Students of the University of Santiago de Compostela in the face of functional diversity of their peers - M. Emma Mayo Pais (Universidad de La Rioja, 2021)
To continue previous research, this research is proposed in order to know the ideas and attitudes of students of the University of Santiago de Compostela (USC) towards their peers with functional diversity (disability). The method selected for collecting information has been the survey, using a questionnaire as a tool for data collection. A total of 400 non-disabled students from the USC participated, studying in the different areas of knowledge. The results indicate that USC students express positive ideas and attitudes, of acceptance towards the integration into the university of their peers with functional diversity. Unlike other research, the age, gender and academic year in which they are enrolled did not introduce statistically significant differences in the ideas and attitudes expressed.